VD_FINDINFO Jug / 2014 / 140 vom 5. Dezember 2013 - VD Tribunal cantonal (2013)
ESCROQUERIE, ASTUCE, DESSEIN D'ENRICHISSEMENT, TENTATIVEDROIT PÉNAL, MENACEDROIT PÉNAL, SURSIS À L'EXÉCUTION DE LA PEINE, PRONOSTIC | 146 al. 1 CP, 180 CP, 22 CP, 42 al. 2 CP